CONCEPTUAL METAPHOR IN THE POETRY ENTITLED LOVE SONGS BY SARA TEASDALE - Ni Putu Mitha Karunita; Ida Bagus Gde Nova Winarta; I Wayan English Study Program Faculty of Foreign Juniartha (IKIP Siliwangi, 2022)
The article entitled